Stirrer time effect on optical properties of nanophotonic LiNbO3 - Al-Douri, Yarub; Fakhri, Makram A.; Bouhemadou, Abdelmadjid; Khenata, Rabah; Ameri, Mohammed (Elsevier, 2018)
Lithium niobate (LiNbO3) nanostructures are synthesized on n-silicon substrate by spin coating technique with stirrer times; 8 h, 24 h and 48 h. LiNbO3 is characterized and analyzed by Scanning Electron Microscope (SEM), Atomic Force Microscopy (AFM), X-ray diffraction (XRD) and UV-visible and Photoluminescence (PL). The measurements show that as stirrer time increases, the structures start to crystallize to become more regular distribution, which helps to apply in optical waveguides. In addition, the calculated refractive index and optical dielectric constant are in agreement with experimental data.